Răspuns :
[tex](3a+2b)(3a-2b)=(3a)^{2}-(2b)^{2}=9a^{2}-4b^{2}~(1)[/tex]
[tex]9a^{2}-4b^{2}=12[/tex]
[tex]3a-2b=2[/tex]
[tex]Din~(1)=>3a+2b=(9a^{2}-4b^{2}):(3a-2b)[/tex]
[tex]3a+2b=12:2=6[/tex]
[tex]\boxed{(a+b)(a-b)=a^{2}-b^{2}}[/tex]
[tex]9a^{2}-4b^{2}=12[/tex]
[tex]3a-2b=2[/tex]
[tex]Din~(1)=>3a+2b=(9a^{2}-4b^{2}):(3a-2b)[/tex]
[tex]3a+2b=12:2=6[/tex]
[tex]\boxed{(a+b)(a-b)=a^{2}-b^{2}}[/tex]
9a² - 4b² = 12
3a - 2b = 2
9a² - 4b² = (3a+2b)(3a-2b) = 12
= (3a+2b) × 2 = 12 ⇒ 3a+2b = 12 ÷ 2
3a+2b = 6
3a - 2b = 2
9a² - 4b² = (3a+2b)(3a-2b) = 12
= (3a+2b) × 2 = 12 ⇒ 3a+2b = 12 ÷ 2
3a+2b = 6